Meaty : essays - Irby, Samantha (Vintage Books, 2018)
"The widely beloved, uproarious, first essay collection and the basis for the upcoming FX Studios series from smart, edgy, hilarious, and unabashedly raunchy Samantha Irby. Samantha Irby exploded onto the printed page with this debut collection of essays about trying to laugh her way through failed relationships, taco feasts, bouts with Crohn's disease, and more. Every essay is crafted with the same scathing wit and poignant candor thousands of loyal readers have come to expect from visiting her notoriously hilarious blog, bitchesgottaeat.com"--